Socialism vanquished, socialism challenged : Eastern Europe and China, 1989-2009 - Bandelj, Nina.; Solinger, Dorothy J. (New York ; Oxford : Oxford University Press, 2012)
This volume examines the 20-year aftermath of the 1989 assaults on established, state-sponsored socialism in the former Soviet bloc and in China. It brings together prominent experts on Eastern Europe and China to examine the respective trajectories of political, economic and social transformations that unfolded in these two areas, while also comparing the changes that ensued within the two regions.
Introduction: post-socialist trajectories in comparative perspective / by Nina Bandelj and Dorothy J. Solinger -- Part 1. Re-institutionalizing politics -- Part 2. Recasting state-society relations -- Part 3. Reforming economic systems -- Part 4. Transforming economic behavior -- Part 5. Reshaping social institutions -- Postscript: The fate of the state after 1989: Eastern Europe and China compared / by Nina Bandelj and Dorothy J. Solinger.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Europe, Eastern -- Politics and government -- 1989-; Post-communism -- Europe, Eastern; Europe, Eastern -- Economic policy -- 1989-; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-; Post-communism -- China; China -- Economic policy -- 1976-2000.; China -- Economic policy -- 2000-; Europe de l'Est -- Politique et gouvernement -- 1989-; Postcommunisme -- Europe de l'Est.; Europe de l'Est -- Politique économique -- 1989-; Chine -- Politique et gouvernement -- 1976-2002.; Postcommunisme -- Chine; Chine -- Politique économique -- 1976-2000.; Chine -- Politique économique -- 2000-; POLITICAL SCIENCE -- Political Process -- General; Economic policy; Politics and government; Post-communism; China; Eastern Europe; Government - Non-U.S.; Law, Politics & Government; Government - Europe; Since 1976; E-Books.; E-Reference.